The Role of Love in the Reproduction of Gender Asymmetries: A Case from Postrevolutionary Nicaragua - Hagene, Turid (European Review of Latin American and Caribbean Studies, 2010)
In this article the author explores the dynamics through which emotional dependency could reproduce women’s subordination. The ethnographies presented feature women who work for an income, provide housing, housework and childcare, as well as emotional and sexual support for husbands that often have several women or families. Masculinity in this context does not require family maintenance; ‘absentee patriarchy’ is the term suggested for this gender order. The men who circulate between women that figure as female heads of households manage to construct themselves as a ‘Limited Good’. Women stand out as autonomous and strong, yet fail to profit from their agency in the field of love and intimacy; they go to great lengths in order to keep husbands, even when their behaviour is felt harmful to the women’s honour and emotional wellbeing. The women’s motivation is found to be more emotional than economic.  Resumen: El papel del amor en la reproducción de las asimetrías de género: un caso desde la Nicaragua posrevolucionaria En este artículo la autora explora la dinámica a través de la cual una dependencia emocional puede reproducir la subordinación de las mujeres. Las descripciones etnográficas presentadas muestran a mujeres que se ganan la vida trabajando, a la vez que proporcionan vivienda, se ocupan de las labores domésticas y del cuidado de los niños, así como de brindar apoyo emocional y sexual a sus maridos -los que a menudo tienen varias mujeres o familias. La masculinidad en este contexto no exige la manutención de la familia; sugerimos el término “patriarcado ausentista” para este orden de género. Los hombres que circulan entre mujeres que figuran como cabezas de familia, logran construirse a sí mismos como un ‘Bien Limitado’. Las mujeres se destacan como autonomyas y fuertes; sin embargo, no logran sacar partido de sus esfuerzos en el campo del amor y la intimidad; transgreden sus propios límites con tal de retener a sus maridos, aun cuando sus comportamientos sean considerados perjudiciales para la honra y el bienestar emocional de las mujeres. Los motivos de las mujeres parecen ser más emocionales que económicos.